(untitled) (Tanzania Journal for Population studies and Development, 2021)
This paper examines the factors influencing in-migration, the influence of migration on land tenure and agricultural productivity and the outcomes associated with the influence of migration on land tenure and agricultural productivity. It also assesses intervention measures of land tenure and agricultural productivity. A total of 300 respondents were involved in the study. Data collection and analysis employed both quantitative and qualitative methods. Data was collected by the use of questionnaires, observation and documentary review. The results revealed that migration was one of the factors that influenced land tenure systems and agricultural productivity. Other factors were availability of land for settlement and renting, population increase, the rise of land and crop prices, coupled with the availability of business and social services established in urban centres like Ihanda, Vwawa and Mlowo. These were further influenced by good road and railway infrastructure to neighbouring countries like Zambia and the Democratic Republic of Congo, besides its proximity to highly populated districts like Rungwe, which pushed a lot of people to the district. The presence of relatives who were ready to accommodate new arrivals also contributed to the in-migration to the district. The study concludes that migration will continue to influence land tenure and agricultural productivity in the district as long as urbanization is increasing at a rapid rate, and economic opportunities are also increasing compared to neighbouring districts like Ileje. It is recommended that cross-cutting policies should be amended because issues of land tenure and agriculture depend on multiple factors, including migration.